Role of circulating endothelial progenitor cells in the reparative mechanisms of stable ischemic myocardium. (15th April 2018) - Morrone, D.; Felice, F.; Scatena, C.; De Martino, A.; Picoi, M.L.E.; Mancini, N.; Blasi, S.; Menicagli, M.; Di Stefano, R.; Bortolotti, U.; Naccarato, A.G.; Balbarini, A.
Abstract: Background: Mobilization of endothelial progenitor cells (EPCs) into circulation from bone marrow in patients with acute myocardial infarction has strong scientific evidence; less is known about EPC mobilization in patients with stable coronary artery disease (CAD). The aim of this study was to investigate the association of stable ischemic heart disease with EPC levels in tissue and blood. Methods: Fifty-five consecutive patients admitted to a single treatment center for valve or coronary artery bypass grafting (CABG) surgeries were included in the study. Blood samples were collected in the morning before surgery and analyzed by flow-cytometry to determine peripheral EPC levels (EPC/ml). Tissue EPC (CD34 + VEGFR2 +) levels were assessed on a right atrial appendage segment. Results: Mean age was 76 ± 5 years, 48% were men, and 53% had CAD The number of CD34 + VEGFR2 + cells in the tissue of patients with CAD was significantly higher ( p < 0.005) and circulating EPC showed a tendency to be reduced by approximately 20% in peripheral blood of patients with CAD when compared to those without CAD. Conclusion: Patients with stable CAD had higher EPC density values (EPC/mm2) and were more likely to have lower EPC blood levels when compare with normal controls.